FRI0203 Tuberculosis in rheumatic patients treated with biological therapies – is screening enough?. (23rd January 2014) - Romão, V. C.; Saavedra, M. J.; Vieira-Sousa, E.; Costa, M.; Polido-Pereira, J.; Rodrigues, A. M.; Ramos, F.; Macieira, C.; Capela, S.; Resende, C.; Madruga Dias, J.; Ponte, C.; et al.
Abstract : Background: An increased risk of active tuberculosis (TB) has been reported in patients with rheumatic diseases treated with biological therapies, especially anti-TNF monoclonal antibodies. Most TB cases result from an activation of a previous latent infection (LTB). In Portugal, stringent screening guidelines for detection of LTB have been issued and updated since 2006. Objectives: The aim of this study was to analyze TB cases in biological-treated patients from a single center. Methods: We included patients treated with biological therapy and registered in Reuma.pt that had a diagnosis of TB after starting treatment. Results: 510 patients were treated with biologicals, with a total of 736 exposures, 627 of which to TNF inhibitors. There were 3 cases of TB after the start of biological treatment (0.59% of the patients, 0.41% of the exposures; number needed to harm = 170). Two patients had psoriatic arthritis (PsA) and one had juvenile-onset spondyloarthritis (jSpA). At the time of TB diagnosis patients were 27, 48 and 17 years-old and had a disease duration of 5, 18 and 4 years, respectively. The two patients with PsA were treated with infliximab (IFX) and the jSpA patient with adalimumab (ADA). Two of the patients (PsA1 and jSpA) had a complete negative screening panel (2 step tuberculin skin test (TST), IGRA, chest X-ray (CXR) and no epidemiological risk factors) and therefore were not submitted to prior LTB treatment. Both developed miliary TB (and lymph node TB in the jSpA case) 5.1 and 14.5 months after the beginning of treatment (IFX/ADA), respectively. The other patient (PsA2 ) was treated for LTB (isoniazid (INH) for 9 months) because of positive screening (previous history of treated TB 45 years earlier and TST of 20mm), started biological therapy within 5 months of INH therapy and further developed pulmonary TB 18 months later, after contact with a documented TB case. The diagnosis was made via clinical signs and symptoms in all cases, identification of Mycobacterium tuberculosis in the sputum (PsA1 ) and bronchoalveolar lavage (jSpA) in two patients, lymph node histopathology in one case (PsA2 ) and imaging (CXR/CT-scan) in all cases. All patients were treated with quadruple anti-tubercular therapy for 9-15 months, with favorable evolution and resolution of disease. None of the patients re-started biological therapy. Conclusions: In biological-treated rheumatic patients TB occurred even after appropriate screening measures. No particular pattern could be seen in positive cases, except that all three patients were treated with anti-TNF monoclonal antibodies. TB occurred between 5 and 18 months after starting treatment, in patients with positive and negative screening tests, with and without previous LTB treatment. This highlights that even with thorough screening for LTB, there is still a risk of developing active TB at any time after the start of biological therapies, especially with anti-TNF monoclonal antibodies. Thus, close vigilance is mandatory for every patient. Disclosure of Interest : None Declared